Structural And Semantic Features of Logistics Terms in English and Uzbek - Hasanova Aqida Rakhimjon Qizi; Hasanova Aqida Rakhimjon Qizi (Genius Journals, 2021)
In this article there are considered about the structural and semantic features of logistics terms in English and Uzbek. The article presents the necessary solutions to the following tasks: to characterize logistics as a new area of knowledge; get an idea of the features of terms, different approaches to their classification; define the terminological structure of logistics.
Keywords: Logistics terms; new area of knowledge; features of terms; different approaches